2020
DOI: 10.3390/nano10122343
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Pretransitional Effects in C60 Fullerene Nanoparticles and Liquid Crystalline Dodecylcyanobiphenyl (12CB) Hybrid System

Abstract: The report shows the strong impact of fullerene C60 nanoparticles on phase transitions and complex dynamics of rod-like liquid crystal dodecylcyanobiphenyl (12CB), within the limit of small concentrations. Studies were carried out using broadband dielectric spectroscopy (BDS) via the analysis of temperature dependences of the dielectric constant, the maximum of the primary loss curve, and relaxation times. They revealed a strong impact of nanoparticles, leading to a ~20% change of dielectric constant even at x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
4
12
0
Order By: Relevance
“…Such behavior is manifested via pretransitional effects explained within the Physics of Critical Phenomena [4]. For dielectric constant the following general relation describing such behavior can be concluded [18][19][20][21][22][23][24]:…”
Section: Introductionmentioning
confidence: 99%
“…Such behavior is manifested via pretransitional effects explained within the Physics of Critical Phenomena [4]. For dielectric constant the following general relation describing such behavior can be concluded [18][19][20][21][22][23][24]:…”
Section: Introductionmentioning
confidence: 99%
“…Insight into the impact of pretransitional fluctuations on LC systems and their nanocolloids still constitutes a cognitive gap. 21–25…”
Section: Introductionmentioning
confidence: 99%
“…Insight into the impact of pretransitional fluctuations on LC systems and their nanocolloids still constitutes a cognitive gap. [21][22][23][24][25] This paper presents the results of broadband dielectric spectroscopy studies in n-octyloxycyanobiphenyl (8OCB) and its colloids with BaTiO 3 nanoparticles. Studies cover isotropic liquid, nematic, smectic A and solid phases.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the temperature-dependent behavior of the structural relaxation of LC materials is strongly influenced by pre-transitional phenomena in the isotropic phase [ 15 ]. It has also been shown that the addition of nanoparticles disrupts the pre-transitional phenomena present in the isotropic phase [ 76 , 100 ]. With low concentrations of nanoparticles, a cross-over from non-Arrhenius to Arrhenius behavior has been observed in the isotropic phase; further increase in the nanoparticle concentration causes a cross-over from Arrhenius to non-Arrhenius behavior [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that the addition of nanoparticles disrupts the pre-transitional phenomena present in the isotropic phase [ 76 , 100 ]. With low concentrations of nanoparticles, a cross-over from non-Arrhenius to Arrhenius behavior has been observed in the isotropic phase; further increase in the nanoparticle concentration causes a cross-over from Arrhenius to non-Arrhenius behavior [ 100 ]. Hence the difference in in the isotropic and nematic LCE could be understood by the presence of pre-transitional nematic regions and nematic correlations, respectively, and the relative size of these with respect to the length-scale of correlated motions of the relaxation.…”
Section: Resultsmentioning
confidence: 99%